Modern possibilities of urorectal fistula laparoscopic fistuloplasty - Tkachenko, A. I.; Osadchii, D. N.; Lysenko, V. V.; Maksimoskii, V. E.; Lukianchuk, O. V.; Chetverikov, S. G.; Lysachenko, V. V.; Chaika, A. M.; Chistiakov, R. S.; Melenevskii, A. D.; Mashukov, A. A.; Atanasov, D. V.; et al. (Journal of Education, Health and Sport, 2018)
Objective. The aim was to study the laparoscopic fistuloplasty possibility of the urorectal fistula (URF) that has occured after the rectal resectionin patient with colon cancer and to determine the ways to improve the results of the treatment for this complication.Clinical case. Patient N., 60 y. o., underwent the successful laparoscopic fistuloplasty of the URF that has occurred after surgical treatment for colon cancer and adjuvant polychemotherapy.Conclusion. The minimally invasive fistuloplasty is possible and has a good tolerability even in patients with oncopathology after extended pelvic surgical treatment and chemotherapy. Due to the operation specific this kind of surgery should be performed only in center with high laparoscopic and pelvic surgery experience.